2012
DOI: 10.1158/2159-8290.cd-11-0348
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Inhibition Impairs BRCA1/2 Expression and Sensitizes BRCA-Proficient Triple-Negative Breast Cancer to PARP Inhibition

Abstract: PARP inhibitors are active in tumors with defects in DNA homologous recombination (HR) due to BRCA1/2 mutations. The phosphoinositide 3-kinase (PI3K) signaling pathway preserves HR steady state. We hypothesized that in BRCA-proficient triple-negative breast cancer (TNBC), PI3K inhibition would result in HR impairment and subsequent sensitization to PARP inhibitors. We show in TNBC cells that PI3K inhibition leads to DNA damage, downregulation of BRCA1/2, gain in poly-ADP-ribosylation, and subsequent sensitizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
412
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(444 citation statements)
references
References 36 publications
17
412
1
1
Order By: Relevance
“…This activation also was seen with GDC-0941 alone, albeit to a lesser extent. Recent work from breast cancer models similarly showed that PI3Kα siRNA or the pan-class I-selective NVP-BKM120 increased polyADP ribosylation, pSer139 H2AX, pSer2056 PRKDC, and pSer1981 ATM (35,36). The authors noted the absence of Rad51 foci after PI3Kα inhibition or knockdown and speculated that PRKDC activation may represent a feedback response (36).…”
Section: Discussionmentioning
confidence: 97%
“…This activation also was seen with GDC-0941 alone, albeit to a lesser extent. Recent work from breast cancer models similarly showed that PI3Kα siRNA or the pan-class I-selective NVP-BKM120 increased polyADP ribosylation, pSer139 H2AX, pSer2056 PRKDC, and pSer1981 ATM (35,36). The authors noted the absence of Rad51 foci after PI3Kα inhibition or knockdown and speculated that PRKDC activation may represent a feedback response (36).…”
Section: Discussionmentioning
confidence: 97%
“…Although some 'kinase pathways' like the akt/mTOR pathway seems to be involved as well, notably, this pathway acts in concert with tumour suppressors involved in DNA damage response as well as proteins coded for by genes involved in inherited cancer risk syndromes (such as PTEN and TP53). 283,284 Notably, there are cross talks between components of these pathways, and it is likely that different pathways are of variable importance in different tissue compartments. Conceptually, this parallels what we observe for germline mutations and tissue-specific cancer forms.…”
Section: Way Forwardmentioning
confidence: 99%
“…Other novel combinations in clinical testing include PARPis and PI3K inhibitors; preclinical results combining olaparib and the PI3K inhibitor BKM120 demonstrated synergy (54,55). A phase I study combining these two agents has demonstrated anticancer activity of the combination in patients with recurrent HGSC or triple-negative breast cancer (56).…”
Section: New Treatment Strategiesmentioning
confidence: 99%